Space localization algorithm based RSSI in wireless sensor networks - ZHOU Yan; LI Hai-cheng (Tongxin xuebao)
In real measurement environment,some factors of multi-path,diffraction,obstacles,etc.,propagation losses produced location errors in the positioning process by RSSI technology.Through analyzing error range in 3D space,a new spatial locating algorithm ERSS based on RSSI was proposed.The ERSS algorithm had the advantages: locating calculation simplicity,no extra communication cost on the locating process,and no hardware expansion required.Simulation results show ERSS algorithm achievs noticeable improvement over RSSI algorithm on distance locating accuracy and responding time,and it is suitable to be applied on the environment of wireless sensor network nodes with low cost and performance of hardware.